Correlation between salivary ANG-2 level and inflammation activity of oral lichen planus - XIANG Yuanyi, LUO Jingjing, LI Haiyang, WU Zhongting, ZHOU Hongmei (Kouqiang yixue)
Objective To assay the salivary ANG-2 level of oral lichen planus (OLP) patients, and analyze its correlation with inflammatory activity of OLP. Methods Eighty-nine OLP patients were included, and divided into four subgroups as non-erosive asymptomatic (NEA), non-erosive symptomatic (NES), minor-erosive (MIE) and major-erosive (MAE) groups. Fifteen healthy adults were recruited as controls. Whole unstimulated saliva was collected from each participant, and the salivary ANG-2 level was measured by chemiluminescence immunoassays (CLIA) for analysis. Normal oral mucosal tissue, non-erosive and erosive OLP tissues were collected to detect and analyze the expression of ANG-2 positive blood vessels by immunohistochemistry (IHC). Results The baselines of age and gender between OLP and control groups showed no significant difference. Compared to controls, the salivary ANG-2 levels of OLP group, non-erosive and erosive OLP subgroups were significantly higher (P<0.05), in which erosive OLP group was higher than non-erosive OLP group (P=0.022); NES subgroup was slightly higher than NEA (P=0.048), and there was no statistical significance between MIA and MEA subgroups (P=0.067). Spearman correlation analysis showed a positive correlation between salivary ANG-2 level and inflammation activity in OLP patients (r=0.314,P=0.003). The expression of ANG-2 in non-erosive OLP mucosal tissues slightly increased than normal oral mucosal tissue (P>0.05), but there was no significant difference. The expression of ANG-2 in erosive OLP mucosal tissues significantly increased than normal oral mucosal tissue (P<0.001) and non-erosive OLP group (P<0.001). Conclusion There is a certain correlation between salivary ANG-2 level and inflammatory activity of OLP, indicating that salivary ANG-2 level is probable to be one of the inflammatory activity indicators to monitor the state-variation of OLP as a clinical non-invasive method.